Differences in Weed Suppression between Two Modern and Two Old Wheat Cultivars at Different Sowing Densities - Yue Wu; Nianxun Xi; Jacob Weiner; Da-Yong Zhang (Agronomy, 2021)
Crop losses to weeds can be exacerbated in modern agricultural systems because modern crop cultivars have high population yields but low individual competitiveness. High density cropping systems offer the possibility of effectively suppressing weeds by increasing the initial size-asymmetric advantage of crops over the weeds. We tested this hypothesis in an outdoor mesocosm experiment with two old (Cultivar Heshangtou (HST) and Jinbaoyin (JBY)) and two modern (Xihan2 (XH2) and Xihan3 (XH3)) cultivars of spring wheat (Triticum aestivum L.), grown in a uniform pattern at four sowing densities under high weed pressure. Two annuals (Brassica napus and Linum usitatissimum) were used as model weeds sown at the same density in all treatments. Weed growth decreased and wheat yield increased with increasing crop density for all the cultivars, although yield levelled off at the highest densities. The old cultivars suppressed weeds better than the new cultivars at low density, reflecting the decline in individual competitiveness in modern cultivars. At high crop density, however, the modern XH3 suppressed the weeds as well as the old cultivars, supporting the hypothesis that traits that promote weed suppression are different at low vs. high density. Increasing crop density can be an effective way to suppress weed growth in many agricultural systems, and there is great potential for developing genotypes that can do this and produce high yields much better than the cultivars currently available.